Lysimachia dabieshanensis sp. nov. (Primulaceae), a new species from Dabieshan Mountain, China - Liu, Kun; Zhou, Shou-Biao; Chen, Yan-Song; Hong, Xin (Phytotaxa, 2014)
A new species of Primulaceae, Lysimachia dabieshanensis K. Liu & S.B. Zhou, is described and illustrated from Dabieshan mountain, Anhui, China. It is similar to L. melampyroides var. amplexicaulis and L. klattiana in leaf and flower shape, but can be distinguished by its taller plant, connate-perfoliate leaves at lower nodes of stem and branch, and obviously raised veins abaxially.